Influence of behavioral and dietary aspects on children's oral health (Research, Society and Development, 2021)
The purpose of this study was to verify the association of microbiological aspects, behavioral and eating habits that affect the oral health of preschoolers. This is a cross-section of a longitudinal study, with a sample of 42 preschoolers at 30 months of age. A home visit was carried out to conduct an interview on aspects of breastfeeding, early weaning, the child's oral hygiene habits, such as brushing frequency and habits, sharing toothbrushes and kitchen utensils and 24-hour food recall of the preschooler. Was collected 0.5 ml of saliva from the oral floor of the mother and the preschooler using sterile disposable pipettes for culture in a Petri dish. It was observed that there was an association between early weaning (p = 0.046) and bottle use (p = 0.018) with the presence of caries; however, there was no association between the consumption of sugary foods between meals (p = 0.302). The average colony-forming unit (CFU) / ml of S. mutans found in the mothers' saliva was 974421 and the preschool was 135341.9. Extracellular polymer was found in the CFU of samples from 61.90% of mothers and 09.52% of preschoolers. Eating habits such as early weaning and bottle use were associated with the presence of caries. There was no association between microbiological and behavioral aspects that affect oral health and the consumption of sugary foods between meals with the presence of caries in preschoolers.